2017
DOI: 10.1017/s1092852917000463
|View full text |Cite
|
Sign up to set email alerts
|

Brain alterations potentially associated with aggression and terrorism

Abstract: A large proportion of the persons who join terrorist groups as well as lone-acting terrorists have a history of violent behavior or mental disorder that predated their becoming terrorists. This suggests that brain alterations found to occur in violent perpetrators may also be present in a significant percentage of terrorists. After a short delineation of phylogenetically old neuronal networks that are important for the generation of aggressive behavior in inconspicuous brains, this review summarizes structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 99 publications
0
16
0
Order By: Relevance
“…In a similar vein, reduced gray matter in amygdala and PFC regions including the OFC have consistently been associated with trait aggression as well (Ermer et al, 2012). Functional neuroimaging studies corroborate the relevance of this frontolimbic system for the control of aggressive impulses; specifically, reduced IFG-amygdala connectivity is frequently observed in overly aggressive individuals (see Bogerts et al, 2018, for a review). Similar findings have also been obtained for the OFC; amygdala-OFC connectivity shows a negative association with trait anger (Fulwiler et al, 2012).…”
Section: Discussionmentioning
confidence: 75%
“…In a similar vein, reduced gray matter in amygdala and PFC regions including the OFC have consistently been associated with trait aggression as well (Ermer et al, 2012). Functional neuroimaging studies corroborate the relevance of this frontolimbic system for the control of aggressive impulses; specifically, reduced IFG-amygdala connectivity is frequently observed in overly aggressive individuals (see Bogerts et al, 2018, for a review). Similar findings have also been obtained for the OFC; amygdala-OFC connectivity shows a negative association with trait anger (Fulwiler et al, 2012).…”
Section: Discussionmentioning
confidence: 75%
“…Bogerts et al ’s (2018) review of violent offenders also found structural and functional abnormalities in brain regions crucial for empathy and compassion. Similar deficits have been found in individuals with antisocial personality disorder (Blair 2005; Marazziti 2013), and Marazziti (2016) has proposed that psychopathy could be a starting point for researchers trying to make sense of possible psychological profiles and features of terrorists.…”
Section: Socio-environmental and Neurobiological Factorsmentioning
confidence: 99%
“…Recent studies have revealed various socio-environmental and neurobiological factors associated with terrorist behaviour (Box 2).
Socio-environmental and neurobiological factors associated with terrorist behaviour Socio-environmental factors Socio-environmental risk factors that predispose a person to terrorism include (Campelo 2018): family dysfunctionfriendships with radicalised individualsunstable geopolitical environmentsocietal polarisation (unequal socio-economic conditions in the country) Neurobiological factors Violent offenders were found to have the following (Bogerts 2018): decreased grey matter in the orbitofrontal and prefrontal cortexdecreased volume of all temporolimbic structures and the posterior cingulate cortexreduced functional connectivity between the frontal cortex and the limbic areas, anterior insula and posterior cingulate cortexStructural and functional deficits in brain regions crucial for empathy and compassion, similar to those in individuals with antisocial personality disorder, have also been found (Blair 2005; Marazziti 2013).
…”
Section: Socio-environmental and Neurobiological Factorsmentioning
confidence: 99%
See 2 more Smart Citations